Pulso de oxigênio para determinação da produção de calor em vacas leiteiras - Karen Brigitte Diaz Magaña (2019)
The objective of this study was evaluating the efficiency of the oxygen pulse (O 2P) methodology at different measurement times, using a respirometry chamber to estimate heat production in dairy cows. were used eleven dairy cows, (Six of breed Holstein and five ¾ Holstein x ¼ Gyr) with a mean of 100 lactating days, milk production of 23 kg/day and 576.5 ± 70 kg of body weight. A heat production was estimate using the respirometry chamber (EHPRC) and oxygen pulse (EHPO2P) methodology, in which heart rate (HR) was monitored for 4 consecutive days. Oxygen pulse was obtained by simultaneously measuring of HR and oxygen consumption (VO2) during 3, 6, 9, 12, 15, 18, 21 and 24 hours in two consecutive days. Two open flow respirometry chamber for big ruminants was employed to determine VO2 and carbon dioxide production. Data were analysis of repeat measurements, with the methodology of mix models through the PROC MIXED of SAS® (version 9.0) and the maximum restrained likelihood (REML) as the estimation method. Variation between estimate heat production EHPRC and EHPO2Pwas of 10% and was founded a correlation of 70.6% between methodologies. (P=0.03). HR and O2P showed difference (P<0.05) at time of three hours. VO2 showed difference just at 9 and 12 hours of measurements time (P<0.05). The use of the O2P methodology to determine the heat production has a high correlation with the respirometry chamber methodology. However, a minimum of 3 hours of evaluation is necessary to obtain a more accurate estimate.